Functional analysis of candidate genes identified through whole genome sequencing in Caribbean Hispanic families for late‐onset Alzheimer disease: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Wang, Liyong; Cukier, Holly N.; Rajabli, Farid; Hofmann, Natalia K.; Adams, Larry D.; Rodriguez, Vanessa C.; Mena, Pedro Ramon; Garcia‐Serje, Catherine; Silva, Concepcion; Feliciano, Nereida I.; Feliciano‐Astacio, Briseida E.; Acosta, Heriberto; et al.
Abstract: Background: To identify LOAD risk genes in Puerto Ricans (PR), a population underrepresented in genetic studies, linkage analysis of whole genome sequencing (WGS) in 23 multiplex PR families identified a peak on chromosome 9p21 (MLOD = 3.9). The 1‐LOD unit down region spans from 31∼38Mb; identity‐by‐descent (IBD) sharing region spans from 23‐39 Mb. Two genes in the linkage region, UNC13B, located in the center of the linkage peak (35.1∼35.4 Mb), and ELAVL2 (23.7∼23.8 Mb), at the edge of the IBD sharing region, are of interest. Both genes have multiple rare variants with low minor allele frequencies (MAF) and high CADD scores that segregate with LOAD in the families. UNC13B encodes a protein involved in Ca 2+ release at the synapse, and calcium dysfunction has been associated with LOAD. ELAVL2 encodes a neural‐specific protein involved in RNA processing. Method: Recombinant plasmids for testing overexpression ( UNC13B ) and promoter activity ( ELAVL2 ) were made by site‐directed mutagenesis and transfected into the neuronal SH‐SY5Y. Result: Two UNC13B missense variants, rs35199210 (Asp238Glu, CADD = 22, MAF = 0.5%) or rs41276043 (Phe1096Leu, CADD = 26.5, MAF = 0.5%) have been cloned into overexpression vectors and are currently being evaluated for their effect on Ca 2+ release rates. One promoter variant rs542037226 (CADD = 16.6, MAF = 0.03%) in the ELAVL2 demonstrated strong activity (∼200x higher than the empty vector), and the rare allele showed reduced activity compared to the reference allele (10% reduction, p = 0.03). Conclusion: Two potential new LOAD genes with rare variants have been identified within the linkage 9p21 linkage peak. Using segregation and in‐silico analysis we have prioritized rare variants in each gene for testing. Successful demonstration of functional changes in the ELAVL2 variants provide support for this approach. Evaluation of UNC13B variants are underway. Those variants with functional effects will be further evaluated in our inducible pluripotent stem cell models.